Increasing Literacy of Cooperatives and SMEs through Library Digitization of the Ministry of Cooperatives and SMEs - Freddy Yakob (2022)
The internet era's evolution now compels all aspects of life to converge. Literacy, for example, has always been tightly linked to literature. The use of libraries as a storefront for literacy resources is also a cause of concern. As a result, digitization of cooperatives has become a top priority in promoting literacy, particularly among cooperatives and small businesses. This study focused on the digitization process at the Ministry of Cooperatives and Small Businesses Library. Observation of participants was used, with the author acting as a recording device in the process. Planning, digitalization, and finalization are the three key stages of the digitization process. A traditional library can now be accessed online, albeit with limited coverage. It is open to the entire public.